The interaction of publications and appointments: New evidence on academic economists in Germany - Klaus Beckmann; Andrea Schneider (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2009)
Using a new panel dataset comprising publication and appointment data for 889 German academic economists over a quarter of a century, we confirm the familiar hypothesis that publications are important for professorial appointments, but find only a small negative effect of appointments on subsequent research productivity. In fact, a simple theoretical model leads us to hypothesise that no such effect exists for top researchers ("stars"), which is borne out by our estimation results. We also provide some evidence of the effects of the fundamental reform of economics in Germany and of affirmative action procedures.
urn:nbn:de:gbv:705-opus-19437
Keywords: D1; D3; H2; 330; Economics of education; research output; publications; academic career; Wirtschaftshochschule; Wirtschaftswissenschaftler; Hochschullehrer; Erwerbsverlauf; Publikationsanalyse; Wirtschaftsstudium; Personalbeschaffung; Deutschland